Association Between Dimensions of Professional Burnout and Turnover Intention Among Nurses Working in Hospitals During Coronavirus Disease (COVID-19) Pandemic in Iran Based on Structural Model - Karimi, Leila; Raei, Mehdi; Parandeh, Akram (Frontiers in Public Health, 2022)
Purpose: This study was done to assess dimensions of burnout among healthcare workers and its role in the turnover intention during the first wave of the COVID-19 pandemic in Iran based on a structural model. Methods: This descriptive correlational study was performed among 170 healthcare workers in two reference hospitals of COVID 19 in Tehran Province, Iran, from September to December 2020. Data were collected using the Sociodemographic form, Maslach burnout Inventory (MBI), and Turnover Intention Questionnaire (Cammann1979). Data were analyzed with SPSS and Amos software version 22 using independent t-test, ANOVA, and structural equation model. Results: The mean scores for burnout in emotional fatigue, depersonalization, Personal accomplishment dimensions were 25.38 ± 7.55, 9.47 ± 4.40, 34.94 ± 7.80 respectively, moreover for the turnover intention was 6.51 ±3.17. Work position and interest in attending the organization were significantly correlated with the turnover intention (p <0.05). The reduced personal accomplishment was identified as a positive predictor of turnover intention (P = 0.01). Conclusions Feeling of personal accomplishment can play an effective role in preventing front-line nurses from retention during a coronavirus pandemic. Therefore, planning to improve the knowledge and empowerment of healthcare workers, increase resilience, support welfare, and improve the working environment during health crises is recommended.